Approaches for Improvement in Digestive Survival of Probiotics, a Comparative Study - Agnieszka Dudkiewicz; Laura Masmejean; Clement Arnaud; Bukola Adenike Onarinde; Ramana Sundara; Amir Hossein Pour-Taghi Anvarian; Nick Tucker (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to compare approaches commonly recommended in the literature for the improvement of the survival of probiotics in the human digestive tract. The survival of two probiotics, Lactobacillus casei and Bifidobacterium lactis , in the presence or absence of prebiotics, maize starch, fermented milk and upon encapsulation in calcium alginate-chitosan was evaluated. While B. lactis was resistant to stomach juice, but sensitive to duodenal juice, L. casei showed an exactly opposite behaviour. In contrast to other published studies, here the overall digestive survivability of probiotics was not improved significantly by prebiotics, maize starch or encapsulation. However, a significant improvement of the overall survivability of B. lactis (but not L. casei ) during in vitro digestion was noted in milk and fermented milk, possibly due to reduction of the activity of bile against this probiotic. Summarising, no one method could be universally recommended for the improvement of probiotic survivability. Nevertheless, this research indicated that certain probiotic characteristics, such as susceptibility to bile or acid or ability to utilise matrix components as an energy source, could be used in further research to select the most effective approaches to deliver viable cells into lower parts of the digestive tract.